PENDALAMAN PENGUASAAN APOLOGETIKA KRISTEN: INTEGRASI KAJIAN TEOLOGIS, BIBLIKA, DAN HISTORIS DALAM PEMBELAAN IMAN KRISTEN (Tarombo: Journal of Christian Theology, Education, and Ministry, 2026)
ABSTRACT  Christian apologetics plays an important role in strengthening believers’ faith and equipping them to respond to intellectual, theological, and cultural challenges. In contemporary contexts, apologetics is often reduced to argumentative defense, while its deeper function as theological formation, biblical grounding, and historical witness is frequently neglected. This study examines the deepening mastery of Christian apologetics through an integrated theological, biblical, and historical framework. Using a qualitative theological-conceptual method, this research analyzes the theological foundations of apologetics, biblical mandates for defending the faith, and the historical development of apologetic thought in the Christian tradition. The findings show that Christian apologetics should not be understood merely as rational defense, but as a holistic discipline that integrates truth, faithfulness, humility, and witness. This study contributes a conceptual framework for apologetics that is biblically grounded, theologically coherent, historically informed, and practically relevant for the church, theological education, and Christian public engagement. The original contribution of this study lies in proposing an integrative theological-biblical-historical model that positions Christian apologetics not merely as rational defense, but as a formative framework for faith, witness, and public engagement. Keywords: Christian apologetics, theology, biblical studies, church history, faith defense  ABSTRAK  Apologetika Kristen memiliki peran penting dalam memperkuat iman orang percaya dan memperlengkapi mereka untuk menghadapi tantangan intelektual, teologis, dan kultural. Dalam konteks kontemporer, apologetika sering kali direduksi hanya sebagai pembelaan argumentatif, sementara fungsi yang lebih mendalam sebagai pembentukan teologis, penguatan biblika, dan kesaksian historis sering terabaikan. Penelitian ini mengkaji pendalaman penguasaan apologetika Kristen melalui integrasi kajian teologis, biblika, dan historis. Dengan menggunakan metode kualitatif teologis-konseptual, penelitian ini menganalisis dasar teologis apologetika, mandat biblika dalam pembelaan iman, serta perkembangan historis pemikiran apologetika dalam tradisi Kristen. Hasil penelitian menunjukkan bahwa apologetika Kristen tidak boleh dipahami hanya sebagai pembelaan rasional, tetapi sebagai disiplin iman yang holistik, yang mengintegrasikan kebenaran, kesetiaan, kerendahan hati, dan kesaksian hidup. Penelitian ini memberikan kontribusi berupa kerangka konseptual apologetika Kristen yang berakar pada Alkitab, koheren secara teologis, sadar sejarah, dan relevan bagi gereja, pendidikan teologi, serta keterlibatan Kristen di ruang publik. Kontribusi orisinal penelitian ini terletak pada perumusan model integratif teologis-biblika-historis yang menempatkan apologetika Kristen bukan hanya sebagai pembelaan rasional, tetapi sebagai kerangka pembentukan iman, kesaksian, dan keterlibatan publik. Kata kunci: apologetika Kristen, teologi, biblika, sejarah gereja, pembelaan iman
Keywords: apologetika Kristen; Teologi; biblika; sejarah gereja; pembelaan iman